IMPLEMENTASI METODE ROLE PLAYING TERHADAP KEPERCAYAAN DIRI SISWA PADA PEMBELAJARAN SBdP SD NEGERI 1 GAJAH MATI - lusi aprilin; Robert Budi Laksana; Noviati Noviati (Jurnal Tunas Pendidikan, 2026)
The aim of this research is to find out an overview of the implementation of the Role Playing Method on students' self-confidence in SBdP learning at SD Negeri 1 Gajah Mati. Qualitative research is descriptive research that tends to use analysis. Qualitative research is exploratory in nature. This research discusses the results of data analysis carried out in the form of qualitative data. This research was carried out at SD Negeri 1 Gajah Mati District. Tripe Supat Kab. Musi Banyuasin which is located on Jl. Pelembang Jambi District. Tripe Supat, Kab. Musi Banyuasin Gajah Mati Village. In implementing the role playing method on student self-confidence there are 3 stages, namely the planning stage, implementation stage and evaluation stage. This research was conducted at SD Negeri 1 Gajah Mati District. Tripe Supat Kab. Musi Banyuasin, this research aims to find out the description of the implementation of the Role Playing Method on students' self-confidence in SBdP learning at SD Negeri 1 Gajah Mati on the topic of regional dance floor patterns. During the data collection process, researchers collected data by observing, interviewing, and taking notes. Based on the results of research conducted by researchers regarding the implementation of the role playing method on student self-confidence in SBdP learning at SD Negeri 1 Gajah Mati, it can be concluded that: In implementing the role playing method on student self-confidence there are 3 stages, namely planning, implementation stage and evaluation stage before implementing it. role playing method the teacher prepares or carries out planning in compiling learning tools, one of the learning tools prepared is the Learning Implementation Plan (RPP) which is guided by the 2013 curriculum.